Hubungan Kedisiplinan dengan Performa Pemain Futsal Porda Kabupaten Bogor - Prasyahaja, Sugiat; Munajat Saputra, Yudha; Safari, Indra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The aim of this research is to determine the relationship between discipline and the performance of Bogor district regional futsal players. This type of research is quantitative using a descriptive observational research design. The sample in this study consisted of 20 people. The statistical test used is the correlation test. Based on the results of the data processing that has been carried out, it can be seen that the Sig. (2-tailed) 0.032 < 0.05, so it can be stated that there is a significant correlation between the Discipline variabel and the Futsal Performance variabel in Bogor Regency. This finding is significant as it suggests that an increase in discipline can lead to a corresponding increase in futsal performance. In conclusion, discipline has a direct correlation with improving the performance of futsal athletes on the field, a finding that underscores the importance of discipline in enhancing futsal performance. Keywords: discipline, futsal, performance